The Effect of Work Environment on Work Engagement Mediated by Job Satisfaction: A Study of Junior High School Teachers in Bekasi - Reski Tiara; Wulan (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to examine the influence of the work environment on teachers' work involvement with job satisfaction as a mediating variable. The approach used is quantitative with the type of explanatory research. Data analysis was carried out using the Structural Equation Modeling method based on Partial Least Squares (SEM–PLS), which is suitable for complex models and data that are not fully distributed normally. The population in this study is junior high school (SMP) teachers in Bekasi City, with a sample of 260 respondents selected through purposive sampling techniques. The results of the study show that the work environment does not have a direct effect on teacher work involvement. However, the work environment has a positive effect on job satisfaction, and job satisfaction has a significant influence on job engagement. In addition, job satisfaction has been shown to mediate the relationship between work environment and work engagement. These findings confirm the importance of job satisfaction as a psychological factor that bridges the influence of the work environment on teacher engagement. This research provides practical implications for schools to create a conducive work environment to increase teacher satisfaction and engagement. Further research is suggested to add work motivation variables and expand the scope of regions or education levels to obtain more comprehensive results.